Noticeable enhancement in NH3 sensing performance of nebulizer spray pyrolysis deposited SnO2 thin films: An effect of Tb doping. (June 2021) - Maheswari, S.; Karunakaran, M.; Hariprasad, K.; Kasirajan, K.; Poul Raj, I. Loyola; Chandrasekar, L. Bruno; Alshahrani, T.; Shkir, Mohd; AIFaify, S.
Abstract: Rare metal Terbium (Tb) doped SnO2 (SnO2 :Tb) films were fabricated via spray pyrolyzed method with different doping concentrations. The effects of terbium doping concentration on its microstructural, optical, photoluminescence, and room temperature ammonia vapor sensing properties were reported. The crystallite size of the prepared Tb-doped tin oxide films decreases with an increase in doping concentrations. The obtained crystallite size ranges from 12 – 9 nm. The terbium incorporation was confirmed by EDS and elemental mapping. The bandgap values are enhanced as the concentration of Tb doping increases. The high gas response of 79% with fast response/recovery of 31/11 s, respectively is reported for 25 ppm of ammonia at room temperature for 5% Tb doped sample. The gas sensing cycle test shows the excellent sensitive behavior of the films without any decrease upon 5 repeated cycles. The stability of the sample was also checked for a corresponding Tb 5% doped sample, which revealed a stable response even for 50 days. Graphical abstract: Image 1 Highlights: Novel SnO2 :Tb thin films were fabricated facilely by nebulizer spray pyrolysis technique. XRD study confirm monophasic rutile tetragonal films fabrication at all Tb contents. Energy gap was enhanced from 3.63 to 3.76 eV on Tb doping in SnO2 . The highest response/quick recovery time of 31s/11s was noticed for 5 wt% SnO2 :Tb films at 300K. The stability of 5 wt% SnO2 :Tb film was tested and noticed a stable response even for 50 days.